Subjects in Austronesian: Evidence from Kelabit - Hemmings, C (Oxford University Press, 2021)
In LFG, grammatical functions are primitives of the theory and treated as both fundamental and universal. However, there is a long standing debate in the wider literature as to whether grammatical functions should be considered universal or language specific/construction-specific notions. Western Austronesian languages have played a large role in this debate on account of their unusual verbal morphology and the split in typical subject properties between the actor semantic role and the argument privileged by the verbal morphology. In this chapter, Hemmings addresses the debate in relation to empirical data from the Kelabit language of Northern Sarawak. She argues that the Kelabit data provides a number of arguments for treating the privileged argument as subject, and the actor as an object in non-actor voice constructions. This has important implications for the treatment of subjects crosslinguistically, Western Austronesian verbal morphology and linking theories.